Long-term subthalamic nucleus stimulation improves sensorimotor integration and proprioception. Issue 9 (24th April 2013) - Wagle Shukla, Aparna; Moro, Elena; Gunraj, Carolyn; Lozano, Andres; Hodaie, Mojgan; Lang, Anthony; Chen, Robert
Abstract : Objective: Sensorimotor integration is impaired in patients with Parkinson's disease (PD). Short latency afferent inhibition (SAI) and long latency afferent inhibition (LAI) measured with transcranial magnetic stimulation (TMS) can be used to measure sensorimotor integration. Subthalamic nucleus (STN) deep brain stimulation (DBS) has been found to restore these abnormalities, but the time course of these changes is not known. We prospectively evaluated the short-term and long-term effects of STN DBS on SAI, LAI and proprioception. We hypothesised plasticity changes induced by chronic stimulation are necessary to normalise sensorimotor integration and proprioception. Methods: Patients with PD were studied preoperatively, at 1 month and more than 6 months postoperatively. SAI was tested with median nerve stimulation to the wrist preceding TMS pulse to motor cortex by ∼20 ms and LAI by 200 ms. Proprioception (distance and spatial errors) in the arm was quantitatively assessed. For postoperative assessments, patients were studied in the medication-off/stimulator-off, medication-off/stimulator-on, medication-on/stimulator-off and medication-on/stimulator-on conditions. Results: 11 patients with PD and 10 controls were enrolled. Preoperatively, SAI and proprioception was abnormal during the medication-on conditions and LAI was reduced regardless of the medication status. STN DBS had no significant effect on SAI, LAI and proprioception at 1 month. However, at 6 months SAI, LAI and distance errors were normalised in the medication-on/stimulator-on condition. Spatial error was normalised with DBS on and off. Conclusions: Chronic STN DBS in PD normalises sensorimotor integration and proprioception, likely through long-term plastic changes in the basal ganglia thalamocortical circuit.